Pattern of Abdominal Pain Presenting in a General Outpatient Clinic in Teaching Hospitals of Eastern Nepal - Poudel, M; Bhandari, R; Giri, R; Ghimire, A; Uprety, S (Health Renaissance, 2011)
Introduction: Abdominal pain is a frequent presentation in any general clinic setting. Acid peptic disease, cholelithiasis, parasitic infestations, renal colic, urinary infection, hepatitis, infective diarrhoea, dysmenorrhoea, pelvic pain, gastrointestinal malignancy problems are just a few of the frequently encountered causes of these presentations. Objectives: 1.To describe the pattern of clinical presentations of abdominal pain in a general clinic,2.To identify socio-demography profile of the patient presenting with abdominal pain. Methods: This was a cross-sectional study conducted in the general outpatient department (GOPD) of (BPKIHS) a teaching hospital for a period of three months. The record of all abdominal pain cases presenting to GOPD together with the diagnosis recorded by various doctors of GOPD. Results: The greater prevalence of pain abdomen in female (55%) were 20-39 years group and in male (35%) were in 40-59 years group. When compared to all cases of abdominal pain in which females (58%) were predominant more in this study, the most common site for pain was central abdomen. Conclusion: The study showed that the female gender were predominant in the case of abdominal pain compare to male group and according to the occupation house were predominant. Keywords: abdominal pain; BPKIHS; pain. DOI: 10.3126/hren.v9i1.4359 Health Renaissance, 2011: Vol.9 No.1:31-34